2011
DOI: 10.1007/s11060-011-0591-8
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of bevacizumab dose response relationship in U87 brain tumors using magnetic resonance imaging measures of enhancing tumor volume and relative cerebral blood volume

Abstract: Despite the early promising results with the anti-angiogenic agent, bevacizumab, to prolong time to progression in patients with brain tumors, the optimal dose and drug combinations have not yet been defined. The purpose of this study was to characterize the bevacizumab dose–response relationship for brain tumors by measuring the contrast-agent enhanced tumor volumes and relative cerebral blood volume (rCBV) using dynamic susceptibility contrast (DSC) imaging. The studies, performed in the U87 brain tumor mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 27 publications
1
18
0
Order By: Relevance
“…Furthermore, bevacizumab treatment attenuated the angiogenic potential of the U87MG cells, drastically decreasing the number and coverage area of the microvessel sprouts. These trends of the sprout induction by cancer cells and sprout attenuation by anti- VEGF treatment are in agreement with previous in vivo reports, 22,26 and demonstrate that this microvessel model is appropriate for the assessment of drugs targeting cancer angiogenesis.…”
Section: Cancer Angiogenesis Assaysupporting
confidence: 92%
“…Furthermore, bevacizumab treatment attenuated the angiogenic potential of the U87MG cells, drastically decreasing the number and coverage area of the microvessel sprouts. These trends of the sprout induction by cancer cells and sprout attenuation by anti- VEGF treatment are in agreement with previous in vivo reports, 22,26 and demonstrate that this microvessel model is appropriate for the assessment of drugs targeting cancer angiogenesis.…”
Section: Cancer Angiogenesis Assaysupporting
confidence: 92%
“…Results suggested that rCBV decreased with treatment as early as 2 days after therapy, but changes in enhancing tumor volumes from post-contrast T 1 -weighted images were delayed in comparison. In a subsequent study they compared bevacizumab (5 mg/kg) to combination therapy with irinotecan (20.83 mg/kg) and observed a rCBV decrease between 4 and 6 days after therapy, followed by a rebound effect [38]. The authors suggest this may be indicative of the ‘vascular normalization window’, which was further supported by histological visualization of the vessel densities, which were found to be similar between the bevacizumab and control groups.…”
Section: Imaging Biomarkers For Malignant Glioma Response To Antiangimentioning
confidence: 92%
“…Pechman et al . have used rCBV as a measure of therapeutic responses to bevacizumab and combination therapy in a U87 brain tumor murine model [38]. In one study, they used different concentrations of bevacizumab, 0.0, 2.5, 5.0 and 10.0 mg/kg, to determine the potential effects on tumor volume and rCBV [38].…”
Section: Imaging Biomarkers For Malignant Glioma Response To Antiangimentioning
confidence: 99%
See 1 more Smart Citation
“…One possible explanation for this is that BEV, a humanized monoclonal antibody to VEGF, does not influence VEGF in a rat model. However, available data show that BEV does demonstrate therapeutic efficacy in orthotropic U87 models in athymic rats [3133] as it was shown to cause a dose-dependent decrease in the relative cerebral blood volume (rCBV) as well as a decrease in the rate of tumor growth [31, 32]. BEV was also shown to influence brain tumor perfusion as assessed by ferumoxytol MRI in rats with U87 gliomas [31, 32, 34].…”
Section: Discussionmentioning
confidence: 99%